The Role of Training Courses in Developing Secondary School Principals Performance in Makkah City from the teachers’ point of view - Almalki, Adel Hosni; Almalki, Fahad Abdulrahman (Journal of Educational and Psychological Sciences, 2022)
The purpose of the study is to investigate the role of training courses in developing secondary school principal’s performance in Mecca city as perceived by teachers; as well as exploring the significant differences about those courses in in developing secondary school principals performance in Mecca city according to (major, scientific qualifications and years of experience). The study adopted the descriptive analytical approach by the questionnaire to collect data. The population consisted of secondary school teachers in Mecca City, and the study tool was administrated on a sample of (350) teachers. The study reached several results, the most important of which are: The role of training courses in developing the performance of secondary school principals in Mecca city is in a big degree in all domains except for the local community domain, where it came to an average degree in favor of those with (5- 10) years and (10) years and over. Further, there are significant statistical differences according to the academic qualification variable in (teachers, school facilities and equipment) domains in favor of graduate studies, and in the domain (school activities) the differences were in favor of those with a bachelor’s degree, as well as there is significant statistical differences in the two domains of (students and school activities) attributed to major in favor scientific majors.